Internationalization of service-oriented companies: Case study research into a hospitality group - Carvalho,Luísa (2014)
The service sector has grown in importance in recent years mainly because it contributes towards economic growth and job creation in many countries. As yet, the services sector has been the subject of little research and few empirical studies, especially within the field of innovation. Moreover, the specific features of services make it difficult to study their internationalization, notably in tourism companies. The purpose of this study is twofold. Firstly, to present a literature review of internationalization in services and hospitality companies in particular. Secondly, to discuss a case study focusing on the largest Portuguese hospitality group (Pestana Group). This allows us to formulate hypotheses that support empirical study and make some important observations regarding service-oriented companies.